CONSUMER DECISION MODEL: PRICE PERCEPTION, PRODUCT QUALITY, BRAND IMAGE INFLUENCE DECISIONS TO PURCHASE SMARTPHONE iPhone IN INDONESIA - Muhammad Misbahul Munir; Titi Nugraheni; Misdiyono (STABILITY : Journal of Management and Business, 2025)
The purpose of this study is to analyze the factors that influence consumer purchasing decisions on iPhone Smartphone products in Indonesia. The data analysis method used is quantitative primary data. The data used in this study used a questionnaire instrument via Google Form from 100 respondents. The research data was processed using the SPSS Program application. The sampling method in this study was non-probability sampling with a purposive sampling technique. The results of the study indicate that price perceptions influence purchasing decisions on iPhone Smartphones in Indonesia, but product quality and brand image do not influence purchasing decisions on iPhone Smartphones in Indonesia.